Differences in Baseline Characteristics and Access to Treatment of Newly Diagnosed Patients With IPF in the EMPIRE Countries - Kolonics-Farkas, Abigél Margit; Šterclová, Martina; Mogulkoc, Nesrin; Lewandowska, Katarzyna; Müller, Veronika; Hájková, Marta; Kramer, Mordechai; Jovanovic, Dragana; Tekavec-Trkanjec, Jasna; Studnicka, Michael; Stoeva, Natalia; Littnerová, Simona; et al. (Frontiers in Medicine, 2021)
Idiopathic pulmonary fibrosis (IPF) is a rare lung disease with poor prognosis. Diagnosis and treatment possibilities are dependent on the countries’ health systems. Hence, comparison between countries is difficult due to data heterogeneity. Our aim was to analyse IPF patients in Central and Eastern Europe using the uniform data from the European Multipartner IPF registry (EMPIRE) which at the time of analysis involved ten countries. Newly diagnosed IPF patients (N=2492, between 06 March 2012 and 12 May 2020) from the Czech Republic (N=971, 39.0%), Turkey (N=505, 20.3), Poland (N=285, 11.4%), Hungary (N=216, 8.7%), Slovakia (N=149, 6.0%), Israel (N=120, 4.8%), Serbia (N=95, 3.8%) Croatia (N=87, 3.5%), Austria (N=55, 2.2%) and Bulgaria (N=9, 0.4%) were included. Baseline characteristics, smoking habit, comorbidities, lung function values, CO diffusion capacity, HRCT pattern, comorbidities and treatment data were analysed. Patients were significantly older in Austria than in the Czech Republic, Turkey, Hungary, Slovakia, Israel and Serbia. Ever smokers were most common in Croatia (84.1%), least frequent in Serbia (39.2%) and Slovakia (42.6%). Baseline FVC was >80% in 44.6% of the patients, between 50-80% in 49.3%, and <50% in 6.1%. The highest proportion of IPF patients with FVC>80% were registered in Poland (63%), while the least was in Israel (25%). Typical UIP pattern HRCT was present in 67.6% of all patients, ranging from 43.5% (Austria) to 77.2% (Poland). The most common comorbidities were cardiovascular and gastrointestinal diseases, with significant inter-country differences. The majority of patients received antifibrotic therapy; 37.4% used pirfenidone (range 7.4-39.8% between countries) and 34.9% nintedanib (range 12.6-56.0% between countries) treatment. In 6.8% of the cases, a therapy switch was initiated between the two antifibrotic agents. Only 35.5% of all patients did not receive any antifibrotic therapy. Significant differences in IPF patient characteristics and access to antifibrotic therapies exist in EMPIRE countries which needs further investigation and strategies to improve and harmonize patient care and access to therapy in this region.